2020
DOI: 10.1002/er.5777
|View full text |Cite
|
Sign up to set email alerts
|

Methanol and proton transport through chitosan‐phosphotungstic acid membranes for direct methanol fuel cell

Abstract: Composite chitosan-phosphotungstic acid membranes were synthesized by ionotropic gelation. Their liquid uptake is higher for thin membranes (23 ± 2 μm), while it is lower ($70%) for thicker membranes (50-70 μm). Polarization curves recorded using single module fuel cell at 70 C allowed to estimate a peak power density of 60 mW cm −2 by using 1 M as methanol and low Pt and Pt/Ru loadings (0.5 and 3 mg cm −2) at the cathode and at the anode, respectively. Electrochemical impedance spectroscopy was used to estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…CS/PTA hybrid inorganic-organic membranes were morphologically characterized at the microscale by SEM. In previous works, it has been demonstrated that PEMs for hydrogen-fed and methanol-fed low-T fuel cells can be successfully synthesized through ionotropic gelation method [ 21 , 22 , 24 ]. These PEMs were compact and flaw-free, without the presence of micro/macro voids that can negatively affect cell performance.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…CS/PTA hybrid inorganic-organic membranes were morphologically characterized at the microscale by SEM. In previous works, it has been demonstrated that PEMs for hydrogen-fed and methanol-fed low-T fuel cells can be successfully synthesized through ionotropic gelation method [ 21 , 22 , 24 ]. These PEMs were compact and flaw-free, without the presence of micro/macro voids that can negatively affect cell performance.…”
Section: Resultsmentioning
confidence: 99%
“…This result can be explained by considering that, at 250 mV, both electrode reactions have enough overpotential to be fully activated and, therefore, voltage drop is essentially due to the ohmic losses. To understand the reason why it is important to insert an inductance in the EEC to model the electrochemical behavior of the DMFC depending on the impedance spectrum cell voltage, we can consider the MOR as a two-step reaction, based on the following steps [ 24 ]: with k 1 and k 2 the rate constants of the two steps considered for the overall MOR. In particular, Reaction (6) is the methanol oxidation, involving four moles of electrons, which leads to the adsorption of intermediate CO species, whilst Reaction (7) involves the oxidation of CO ads to CO 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is interesting to note, by looking at the inset of Figure , that an inductive loop is present in the low-frequency range of the EIS spectrum of as-polished AZ31. The presence of an inductive loop in the EIS spectrum is typically related to the electrochemical processes that involve more than one reaction step, where one step comprises the formation of adsorbed species on the surface leading to a dependence of reaction kinetics on the electrode surface coverage. ,, This behavior is usually observed in the case of pure Mg and Mg-alloy electrodes, for which the oxide/hydroxide film that spontaneously grows on the surface is quite incoherent and does not cover all of the substrate surface, not offering good corrosion protection to the metal, mostly in acidic or neutral environment, as HS. Moreover, the cathodic process usually coupled to the Mg oxidation is the water reduction that leads to gaseous HE that typically occurs following a multistep kinetic path, involving the presence of adsorbed species. , …”
Section: Resultsmentioning
confidence: 99%